Lethal necrotising pneumonia in young imunocompetent patient caused by staphylococcuc aureus carrying gene for pantonvalentine leukocidin - Irena Piltaver-Vajdec (Zdravniški Vestnik, 2006)
Background: Staphylococcus aureus (S. aureus) is a major cause of hospital-acquired infections. It secretes many exotoxins, in less then 5 % also Panton-Valentine leukocidin (PVL). S. aureus carrying PVL genes is mainly associated with necrotic lesions of skin and mucosa and can cause severe necrotising community-acquired pneumonia. Methods: We describe a case of a 30-year-old patient with a history of furunculosis who was admitted to our hospital with atypical lower abdominal pain. A clinical picture of acute abdomen developed and he was operated with no intraabdominal pathology found. A periprocedural respiratory insuficiency and later septic shock developed. S. aureus and Streptococcus pneumoniae were isolated from blood cultures and tracheal aspirate. In spite of all measures taken, high ventilatory support and targeted antibiotic treatment, severe pulmonary dysfunction with bilateral pneumothorax developed and the patient died of respiratory failure. Later genes encoding PVL were found in the isolated strains of S. aureus. Conclusions: Severe progressive necrotising pneumonia with high mortality can be caused by PVL positive S. aureus in imunocompetent patients. To prevent the future spread of PVL positive S. aureus infection, the measures as known for methicillin-resistant S. aures, should probable be taken.